Beyond average preparedness: a quantile analysis of earthquake mitigation behaviors among homeowners - Nkouaga, Florent (Frontiers in Environmental Economics, 2025)
IntroductionThis study investigates earthquake preparedness among homeowners in eight states affected by the New Madrid Seismic Zone, using the 2024 NAIC earthquake survey data.MethodsApplying weighted Ordinary Least Squares (OLS) and quantile regression analyses, the research explores how risk perception, community engagement, and earthquake awareness influence preparedness across varying readiness levels.ResultsResults highlight community engagement as the strongest predictor across all preparedness quantiles, emphasizing its role particularly at higher preparedness levels. Significant interaction effects were observed between earthquake awareness and home value, with heightened preparedness evident among informed, higher-value property owners. Conversely, the interaction between income and tenure indicates diminishing preparedness among higher-income, long-term residents, suggesting complacency effects.DiscussionThese findings underscore the need for differentiated preparedness strategies that accommodate varying socioeconomic conditions and preparedness levels. This nuanced approach offers policymakers critical insights for enhancing resilience by tailoring interventions to specific homeowner segments, thereby addressing overlooked non-linear and interactive effects often masked by traditional average-based methods.